Stalling, straining, severing, shallowing, simulating: how politicization can negatively affect sustainability transformation - Bornemann, Basil; Strassheim, Holger; Weiland, Sabine (Frontiers in Political Science, 2025)
The relationship between politicization and sustainability transformation is complex and multifaceted. Politicization is often viewed as a catalyst for sustainability transformations. Through contestation and mobilization of societal actors, it provides the impetus for broad and deep social change, bringing societies onto more just and ecologically sustainable pathways. At the same time, politicization can also have detrimental effects, potentially creating fatigue among the public, fostering division rather than unity, and undermining the public support and engagement necessary for effective change. This article aims to contribute to a deeper understanding of the complex relationship between politicization and transformation. To this end, we focus specifically on the negative effects, i.e., how politicization undermines sustainability transformations. Drawing on empirical examples of “politicized transformation,” we identify five different mechanisms by which politicization can stall, strain, sever, shallow, or simulate transformation efforts. We discuss how these mechanisms interact over time to form broader dynamics that undermine or obstruct sustainability transformations and point to potential strategies to counteract these dynamics.